Aquatic aerobic exercise and physical fitness: from scientific foundations to practical applications - Luana Siqueira Andrade; Cristine Lima Alberton (Revista Brasileira de Atividade Física e Saúde)
Introduction: The aquatic environment offers broad potential for physical training, providing an advantageous alternative, especially for individuals who have difficulties performing exercises on land. In this sense, the literature on aquatic exercise for health promotion has grown significantly. Objective: To present accessible knowledge related to the prescription of aquatic aerobic training in the vertical position, aiming to offer a comprehensive understanding from the scientific foundations to the practical applications for professionals who work with aquatic modalities. Development: In this review, we begin by summarizing the physical properties of the aquatic environment and their effects on the immersed human body. We discuss how buoyancy and drag force influence the biomechanics of movements in water and how hydrostatic pressure and thermal conductivity affect physiological parameters. Then, we address the main possibilities for prescribing aerobic exercises in the aquatic environment, highlighting the advantages and disadvantages of each intensity control parameter while considering differences from the land environment. Finally, we present the findings from aerobic training programs on physical fitness outcomes in young and older adults. The available evidence suggests that aerobic training in the aquatic environment may exhibit characteristics and adaptations similar to multicomponent training in previously inactive individuals. Final Considerations: We expect that aquatic professionals will “immerse themselves” into the knowledge related to aquatic exercise, as this will allow them to optimize the effectiveness of training programs in this environment, promoting health and well-being among practitioners.